1993
DOI: 10.1111/j.1532-5415.1993.tb06942.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐Deprenyl in the Treatment of Mild Dementia of the Alzheimer Type: Preliminary Results

Abstract: L-deprenyl did not have a measurable impact on behavior or cognitive function over a 2-month period in this group of subjects with mild DAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…We have previously reported the interim results of our study after 2 months of treatment with L‐deprenyl 36 . Unlike these prior reports, the interim (2 month) results of this study detected no evidence for any L‐deprenyl effect on any clinical or neuropsychological measure 36 …”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…We have previously reported the interim results of our study after 2 months of treatment with L‐deprenyl 36 . Unlike these prior reports, the interim (2 month) results of this study detected no evidence for any L‐deprenyl effect on any clinical or neuropsychological measure 36 …”
Section: Discussioncontrasting
confidence: 65%
“…We have previously reported the interim results of our study after 2 months of treatment with L-de-~r e n y 1 .~~ Unlike these prior reports, the interim (2 month) results of this study detected no evidence for any L-deprenyl effect on any clinical or neuropsychological measure. 36 The intent of this 15-month evaluation was to examine what effect L-deprenyl might have over a longer period of time in subjects with DAT. The only measure that showed any evidence of a drug effect was, interestingly enough, the total score on the BPRS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our result showed that INH treatment considerably inhibited Mao-b activity in APP/PS1 mice. Interestingly, the Mao-b inhibitors, such as selegiline, have been shown to possess the beneficial effects on cognitive impairment in AD patients ( Burke et al, 1993 ; Tolbert and Fuller, 1996 ; Filip and Kolibás, 1999 ). Therefore the inhibitory effect of INH on Mao-b may also contribute to the therapeutic effect on memory impairment in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs as diverse as the non-steroidal anti-inflammatory indomethacin,20 the monoamine oxidase inhibiter selegiline,21 and the peptidergic nootropic drug cerebrolysin22 have been investigated in short term studies in Alzheimer's disease, but the rationale for their use is not clear. An intriguing observation relates to the effects of nicotine in Alzheimer's disease.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%